2016
DOI: 10.1109/tns.2016.2527831
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Characterization of Optical Frequency Domain Reflectometry Fiber-Based Distributed Sensors

Abstract: We studied the responses of fiber-based temperature and strain sensors related to optical frequency domain reflectometry (OFDR) and exposed to high γ-ray doses up to 10 MGy. Three different commercial fiber classes are used to investigate the evolution of OFDR parameters with dose, thermal treatment and fiber core/cladding composition. We find that the fiber coating is affected by both thermal and radiation treatments and this modification results in an evolution of the internal stress distribution inside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…We observe that HTA, Pl and Pl&C coated fibers exhibit stable C T s as a function of radiation with variation within 1% except for the SMF-B irradiated at 3 MGy where variation is 2%. These results confirm that HTA, Pl and Pl&C are more resistant coating to both temperature and radiation constraints than DAC, for which irradiation was a factor to take in account since it introduces errors of the order of 5% in Fdoped fibers [9].…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…We observe that HTA, Pl and Pl&C coated fibers exhibit stable C T s as a function of radiation with variation within 1% except for the SMF-B irradiated at 3 MGy where variation is 2%. These results confirm that HTA, Pl and Pl&C are more resistant coating to both temperature and radiation constraints than DAC, for which irradiation was a factor to take in account since it introduces errors of the order of 5% in Fdoped fibers [9].…”
Section: Resultssupporting
confidence: 73%
“…Those results have revealed that OFDR is a powerful technique possessing an almost unaffected response by radiations opening the way to the development of new fiberbased systems in radiation environments. However, both in [9] and in [10] it is reported that distributed measurements can be affected by the sensor packaging (including coating, metallic tubes, bridles …) resulting in errors caused by an inaccurate calibration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DOFS emerged with the development of a technique called optical time-domain reflectometer (OTDR). There are three main types of OTDR sensing mechanism, which are based on Brillouin [20][21][22][23][24], Rayleigh [25][26][27][28][29], and Raman scattering [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, fiber packaging influences the OFDR sensor response: radiation changes the mechanical properties of the coating surrounding the fiber core/cladding and can lead to errors in strain or temperature distributed measurements. Irradiations up to 3 MGy, as well as thermal treatments up to the maximum operating temperature of this surrounding coating, have been shown to improve the performances of the sensors under harsh environments [6], [7].…”
mentioning
confidence: 99%